TrnL-trnF copy number is inversely correlated with storage time of Guang Chenpi, the aged sun-dried peels of Citrus reticulata 'Chachi'. (May 2022) - Li, Fang; Lu, Yi; Li, Chan; Huang, Rong; Tian, Enwei; Tan, Eyu; Yang, Zhiye; Li, Hua; Chao, Zhi
Abstract: The medicinal value of Guang Chenpi (GCP), the sun-dried peels of Citrus reticulata 'Chachi', increases significantly with the extension of its storage time, hence its commercial value, which drives the profitable malpractice of faking the years of storage of GCP in market. In this study, we developed a molecular quantification method for determining the storage time of GCP, which is not based on examining chemical composition changes of GCP with time. Instead, we investigated the correlation between the copy number of 6 DNA fragments ( mat K, rbc L, psb A- trn H, ITS2, trn L- trn F, and trn L) and storage time of GCP, and found that trn L- trn F copy number in GCP had a significant inverse correlation with the storage time of the drug. We further validated this finding using commercial samples of GCP. This molecular quantification method based on trn L- trn F copy number can provide a useful means for accurate age estimation of GCP. Graphical abstract: Image 1 Highlights: The relationship between gene copies and storage time of GCP was explored by qPCR. The copies of mat K and other four gene were not correlated with the storage time. The logarithm value of trn L- trn F copy number decreases along with the storage time. trn L- trn F in GCP forms a linear time-quantity curve ( R 2  = 0.9384, P  < 0.001).